Efforts to Strengthen Character Education for Elementary School Students by Utilizing Digital Literacy in Era 4.0 - Rahmi Yulia; Nofia Henita; Ricky Gustiawan; Yeni Erita (RADINKA JAYA UTAMA PUBLISHER, 2022)
This study aims to describe the role of digital literacy in improving and strengthening the character education of elementary school students. The research method used is a descriptive-qualitative method with a literature study approach, data sources are obtained from the results of analysis and conclusions obtained from journals. The results of the analysis of this study are in strengthening the character education of elementary school students in this 4.0 era, digital literacy plays an important role as a supporting medium because the characteristics of students tend to be more interested in technology, the internet, social media and others, and are supported by learning taught in elementary schools that contain the integration of character values in each learning. The conclusion of this study is that the use of digital literacy is able to strengthen the character value of students by being balanced with supervision from parents and teachers in its use.